Plasmid-mediated colistin resistance among human clinical Enterobacterales isolates: national surveillance in the Czech Republic - Zelendova, Marketa; Papagiannitsis, Costas C.; Sismova, Petra; Medvecky, Matej; Pomorska, Katarina; Palkovicova, Jana; Nesporova, Kristina; Jakubu, Vladislav; Jamborova, Ivana; Zemlickova, Helena; Dolejska, Monika; , Working Group for Monitoring of Antibiotic Resistance (Frontiers in Microbiology, 2023)
The occurrence of colistin resistance has increased rapidly among Enterobacterales around the world. We performed a national survey of plasmid-mediated colistin resistance in human clinical isolates by a retrospective analysis of samples from 2009-2017 and a prospective sampling in 2018-2020. The aim of this study was to identify and characterize isolates with mcr genes from various regions of the Czech Republic using whole genome sequencing (WGS). Of all 1932 colistin-resistant isolates analyzed, 73 (3.8%) were positive for mcr genes. Most isolates carried mcr-1 (48/73) and were identified as Escherichia coli (n=44) and Klebsiella pneumoniae (n=4) of various sequence types (ST). Twenty-five isolates including Enterobacter spp. (n=24) and Citrobacter freundii (n=1) carrying mcr-9 gene were detected, three of them (Enterobacter kobei ST54) co-harbored the mcr-4 and mcr-9 genes. Multi-drug resistance phenotype was a common feature of mcr isolates and 14% (10/73) isolates also co-harboured clinically important beta-lactamases including 2 isolates with carbapenemases KPC-2 and OXA-48. Phylogenetic analysis of E. coli ST744, the dominant genotype in this study, with the global collection, showed Czech isolates belonged to two major clades, one containing isolates from Europe, while the second composed of isolates from diverse geographical areas. The mcr-1 gene was carried by IncX4 (34/73, 47%), IncHI2/ST4 (6/73, 8%) and IncI2 (8/73, 11%) plasmid groups. Small plasmids belonging to the ColE10 group were associated with mcr-4 in three isolates while mcr-9 was carried by IncHI2/ST1 plasmids (4/73, 5%) or the chromosome (18/73, 25%). We showed an overall low level of occurrence of mcr genes in colistin-resistant bacteria from human clinical samples in the Czech Republic.